Identification and validation of a major quantitative trait locus for spike length and compactness in the wheat (Triticum aestivum L.) line Chuanyu12D7 - Wang, Mingxiu; Lu, Jing; Liu, Rong; Li, Yunfang; Ao, Donghui; Wu, Yu; Zhang, Lei (Frontiers in Plant Science, 2023)
Spike length (SL) and spike compactness (SC) are crucial traits related to wheat (Triticum aestivum L.) yield potential. In this study, a backcrossed inbred lines (BILs) population segregating for SL/SC was developed by using a commercial variety chuanyu25 as recurrent parent and a backbone parent Chuyanyu12D7. Bulked segregant analysis (BSA) combined with the Wheat 660K SNP array was performed to conduct quantitative trait locus (QTL) mapping. A major and stable SL/SC QTL (designated as QSl/Sc.cib-2D.1) was identified on chromosome 2DS, explaining 45.63-59.72% of the phenotypic variation. QSl/Sc.cib-2D.1 was mapped to a 102.29-Kb interval by flanking SNP AX-110276364 and AX-111593853 using a BC4F2:3 population. Since QSl/Sc.cib-2D.1 is linked to the Rht8 gene, their additive effects on plant type and spike type were analysed. Remarkably, superior allele of QSl/Sc.cib-2D.1 combined with Rht8 can increase SL and TGW, and decrese SC without any apparent trade-offs in other yield-related traits. In addition, the closely linked kompetitive allele-specific PCR (KASP) markers of this locus were developed for marker-assisted selection (MAS) breeding. Four genes within the physical interval were considered as potential candidates based on expression patterns as well as orthologous gene functions. These results laid the foundation for map-based cloning of the gene(s) underlying QSl/Sc.cib-2D.1 and its potential application in wheat ideotype breeding.